UKRAINE, RESETTING OUR MILITARY MIND-SET - Ter Borg, Marlies (International Journal of Research -GRANTHAALAYAH, 2025)
The present deadlock in the Ukraine-Russian War demands some hard thinking, reflection on our military mind-set. When more, more-more-more; more weapons, more money, more sanctions are failing to deliver, a mental turning around can open new perspectives. Here we can build forth on what thinkers through the ages have understood about the War God ‘Mars’. However, let us not forget Minerva, the Goddess who combined wisdom with war That is what the philosopher has to offer: Wisdom ín War. In this article I concentrate on Sun Tzu, a Chinese philosopher from 500 BC whose sayings are still very relevant. “If you know the enemy and know yourself, you need not fear the result of a hundred battles. If you know neither the enemy nor yourself, you will succumb in every battle.” A second philosopher is the German Carl von Clausewitz with his focus on continuation of communication during a war. Do not expect from this article the repetition of well-known facts, nor the revealing of ‘secrets’ known only by the powers that be. The philosopher looks through the day-to-day news, to find principles that have characterized war through the ages. Philosophical ideas, that run counter to contemporary opinion but can offer a practical way out of the deadlock.